2019
DOI: 10.1590/rbz4820180253
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of calcium levels in rations supplemented with vitamin D3 or 25-OH-D3 for broilers

Abstract: An experiment was carried out to verify the response to the Ca reduction levels of diets with different vitamin D sources on performance, bone mineral deposition, serum concentrations, digestibility, carcass characteristics, and meat quality of broiler chickens in the period from 1 to 42 days reared in thermoneutral environment. A total of 504 male broilers with one day of age and average weight of 43.27±1.08 g were housed in climatic chambers and distributed in a completely randomized design. The study consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…The reduction in the levels of dietary Ca, regardless of the sources of vitamin D 3, did not influence (p>0.05) broiler performance in all rearing phases. These results are consistent with those obtained by Li et al (2012) and Tizziani et al (2019)…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reduction in the levels of dietary Ca, regardless of the sources of vitamin D 3, did not influence (p>0.05) broiler performance in all rearing phases. These results are consistent with those obtained by Li et al (2012) and Tizziani et al (2019)…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those reported by several authors (Ledwaba & Roberson, 2003;Fritts & Waldroup, 2005;Rao et al, 2006;Castro et al, 2018; Table 3 -Feed intake (FI), weight gain (WG), and feed conversion ratio (FCR) of broiler chickens reared under heat stress at 1 to 21 and 1 to 42 days of age, fed diets supplemented with different vitamin D sources and decreased levels of calcium. Tizziani et al, 2019), where no significant difference in the performance of broilers due to the sources of vitamin D 3 were observed. Although not significant, a reduction of 2.92% was found in the absolute value of FCR of broilers fed diets containing 25(OH) D 3 (p=0.0568), possibly indicating a trend.…”
Section: -Hydroxycholecalciferol As An Alternative To Vitamin D3 In D...mentioning
confidence: 90%
See 1 more Smart Citation
“…Similar results have been reported by Abdulla et al (2017), who observed that Ca levels did not affect yield, leg, and breast percentages. In another study, the carcase, breast, drumstick, and thigh yields were not influenced by the reduction of Ca up to 30% of the broilers' requirements (Tizziani et al 2019). In the current study, meat quality was not studied and can be considered in future investigations.…”
Section: Carcase Traitsmentioning
confidence: 91%
“…Additionally, Akter et al (2016) noted that the internal organ relative weights of broiler chicks were not impacted by reducing dietary Ca from 10 to 6 g/kg and dietary NPP from 4 to 3 g/kg. Tizziani et al (2019) demonstrated that the carcass yield of broiler chickens was not influenced by reducing Ca levels up to 30% of the requirements. In contrast, El-Faham et al (2019) found that decreasing the dietary Ca and available P to a level equivalent to half of the requirements significantly decreased the dressing and carcass yield in broilers.…”
Section: Resultsmentioning
confidence: 98%